Low-cost composite sodium ferric phosphate positive electrode material, preparation method and application
By using raw materials such as iron concentrate powder and phosphoric acid, combined with ball milling and heat treatment technology, low-cost and high-performance NFPP cathode materials are prepared, which solves the problems of high cost and low sodium storage performance in the existing technology, and achieves significant cost reduction and performance improvement.
Patent Information
- Application Number
- CN202510171917.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-05-02
AI Technical Summary
The existing sodium ion battery positive electrode materials have high cost and low sodium storage performance, making it difficult to have market competitiveness.
Iron concentrate powder is used as raw material, combined with phosphoric acid, oxidant, sodium source and carbon source, and iron phosphate precursor is formed through ball milling and oxidant auxiliary strategies, and converted into high-purity NFPP material through heat treatment.
The raw material cost is significantly reduced, the BOM cost is reduced by 16.3% to 54.6% compared with the existing technology route, and the sodium storage performance and product purity are improved.
Smart Images

Figure CN119911890A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a low-cost composite sodium iron phosphate positive electrode material, a preparation method and an application thereof. Background Art
[0002] Sodium-ion batteries have attracted much attention due to their abundant raw materials, low cost, environmental friendliness, outstanding low-temperature performance, and high safety. In the future, they are expected to completely replace lead-acid batteries and be widely used in energy storage, two-wheeled electric vehicles, and even A00-class electric vehicle markets. Similar to lithium-ion batteries, positive electrode materials are the key to the development of sodium-ion batteries, and therefore have attracted the attention of many researchers.
[0003] Among a large number of potential cathode materials for sodium-ion batteries, sodium iron pyrophosphate compound Na4Fe3(PO4)2(P2O7) (hereinafter referred to as NFPP) is highly anticipated, with high theoretical capacity (129 mAh / g), high average operating voltage (3.1 Vvs.Na + / Na). At the same time, the three-dimensional structure gives it excellent structural stability and fast ion diffusion pathways, which makes the sodium iron pyrophosphate positive electrode have a good cycle life and fast charging capability.
[0004] At present, a large number of patents and literatures have reported on the technical routes of synthesizing NFPP positive electrode materials using iron red, ferric nitrate and ferrous oxalate, and have achieved certain success. However, the iron equivalent price of primary iron sources such as iron red, ferric nitrate and ferrous oxalate as the main raw materials is too high (14,000-31,000 yuan / ton), so the BOM cost is high and it is difficult to be competitive in the market. The use of other cheap iron raw materials, such as ferrous sulfate and ferric chloride, will introduce a large amount of chloride ion and sulfate impurities into the NFPP product, and the product purity and performance are poor. In view of this, it is urgent to develop a low-cost synthesis of high-purity and high-performance NFPP technical route to promote the rapid marketization of NFPP positive electrode materials. Summary of the invention
[0005] In order to overcome the defects of the prior art, the present invention provides a low-cost composite sodium iron phosphate positive electrode material, a preparation method and an application thereof, which can solve the technical problems of high cost and low sodium storage performance of the currently prepared sodium ion battery positive electrode materials.
[0006] The object of the present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a low-cost composite sodium iron phosphate positive electrode material, comprising iron ore powder, a phosphorus source, an oxidant, a sodium source, and a carbon source, wherein the iron content of the iron ore powder is 71-72 wt%.
[0007] The present invention develops an iron ore concentrate powder (component is FeO x, 1≤x≤1.5) as raw materials can significantly reduce the cost of raw materials. Compared with the mainstream ferrous phosphate and ferrous oxalate technical routes, the raw material cost can be reduced by 38.9% and 58.8% respectively.
[0008] In one embodiment, the low-cost composite sodium iron phosphate positive electrode material includes the following raw materials in parts by weight: 20-25 parts of iron ore concentrate powder, 29-52 parts of phosphorus source, 4-5 parts of oxidant, 18-22 parts of sodium source, and 6-8 parts of carbon source.
[0009] This raw material ratio can make the prepared positive electrode material have a higher sodium storage capacity. When the mass of the sodium source exceeds this ratio, the stability of the overall composite structure will decrease. If the sodium source content is lower than this ratio, the sodium storage capacity will decrease.
[0010] In one embodiment, the phosphorus source includes at least one of phosphoric acid, sodium dihydrogen phosphate, pyrophosphoric acid, disodium dihydrogen pyrophosphate, and sodium pyrophosphate.
[0011] In one embodiment, the oxidant includes at least one of nitric acid, sodium nitrate, ammonium nitrate, nitrous acid, sodium nitrite, and ammonium nitrite, and the concentration of the oxidant is 3-10 wt%.
[0012] In one embodiment, the carbon source includes at least one of starch, glucose, sucrose, citric acid, and ascorbic acid.
[0013] In one embodiment, the sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium nitrate, sodium dihydrogen phosphate, disodium dihydrogen pyrophosphate, and sodium pyrophosphate.
[0014] In a second aspect, the present invention provides an application of the above-mentioned low-cost composite sodium iron phosphate positive electrode material in the preparation of a sodium ion battery.
[0015] In the third aspect, the present invention also provides a method for preparing the above-mentioned low-cost composite sodium iron phosphate positive electrode material, comprising the following steps: S1, adding iron ore powder, phosphorus source and oxidant to deionized water in turn and grinding to obtain an iron phosphate precursor; S2, adding a carbon source and a sodium source to the iron phosphate precursor and stirring to obtain a solid-liquid mixed slurry; S3, ball milling / sand milling the solid-liquid mixed slurry to obtain a uniformly dispersed slurry; S4, drying, crushing and sieving the uniformly dispersed slurry in turn to obtain a precursor powder; S5, sintering the precursor powder in an inert gas to obtain the low-cost composite sodium iron phosphate positive electrode material.
[0016] The chemical equations mainly involved in S1 are as follows: The chemical reactions involved are as follows: FeO x +H3PO4+HNO3→FePO4·2H2O+NO↑FeOx +H3PO4+NaNO2→FePO4·2H2O+NO↑ This method uses cheap iron concentrate and low-cost phosphorus source as the main materials. Under the action of an oxidant, the iron source and the phosphorus source are pre-polymerized by ball milling / sand milling to form an iron phosphate precursor. After sodium supplementation, the iron phosphate precursor is converted into NFPP material using a controllable heat treatment technology to synthesize a preparation method for a low-cost sodium ion battery positive electrode composite positive electrode material NFPP / C. The technical route developed by this patent has a simple process, low and stable raw material prices, and a significant cost reduction effect. According to calculations, compared with the currently developed iron red, iron nitrate and iron oxalate technical route processes, the BOM cost alone can be reduced by 16.3%, 35.2% and 54.6% respectively. In addition, compared with the iron nitrate and iron oxalate routes, the technical route process provided by the present invention also has the advantages of low processing difficulty and low exhaust gas pressure.
[0017] In one embodiment, in S2, the solid content in the solid-liquid mixed slurry is 20~50 wt%; in S4, the drying includes air drying and spray drying, the air drying temperature is 70~100°C, the air drying time is 2~10h, the inlet air temperature of the spray drying is 150~250°C, the outlet air temperature is 60~120°C, and the feed rate is 0.5~30 mL / min; in S5, the sintering includes pre-sintering and two-stage sintering, the pre-sintering temperature is 300~400°C, the pre-sintering time is 2~5 h, the two-stage sintering temperature is 480~550°C, and the two-stage sintering time is 6~15 h.
[0018] This temperature range, time range and heating rate range can ensure the stability of the composite material structure and improve the tap density. Above this range will lead to structural instability, and below this range will result in a low tap density.
[0019] In one embodiment, the inert gas is nitrogen, argon, an argon-hydrogen mixture or a nitrogen-hydrogen mixture.
[0020] The main beneficial effects of the present invention are: The present invention develops a process for preparing low-cost ferric phosphate from cheap iron concentrate, which uses iron concentrate and phosphoric acid as main raw materials, adopts ball milling and oxidant-assisted strategies, realizes rapid conversion of iron-phosphorus into ferrophosphorus compound precursor, and then converts it into high-purity NFPP product in subsequent heat treatment.
[0021] In terms of composite sodium iron phosphate positive electrode materials, the gain effect of the present invention is: the technical route developed by the present invention using iron ore concentrate powder as raw material can significantly reduce the cost of raw materials. Compared with the currently developed iron red, iron nitrate and sub-railway oxalate technical route processes, the BOM cost alone can be reduced by 16.3%, 35.2% and 54.6% respectively. In addition, compared with the iron nitrate and sub-railway oxalate routes, the technical route process provided by the present invention also has the advantages of low processing difficulty and low exhaust gas emission pressure.
[0022] In addition, the technical route provided by this patent uses production equipment similar to that used in the production of lithium iron phosphate, has a complete equipment foundation and mature industrialization experience, and shows the potential for large-scale production. The technical route provided by this patent is used to produce polyanion cathode materials, which combines the two major factors of cost and performance, and can comprehensively improve the competitiveness of sodium iron pyrophosphate products. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention will be described in more detail below based on embodiments and with reference to the accompanying drawings, wherein: Figure 1 Scanning electron microscope images of the positive electrode materials prepared in Examples 1-2, Comparative Example 1-1, and Comparative Example 1-3; Figure 2 XRD patterns of the NFPP / C composite cathode materials prepared in Examples 1 and 2; Figure 3 XRD patterns of the composite positive electrode materials prepared in Comparative Examples 1-1, 1-2 and 1-3; Figure 4 The charge and discharge curves of the positive electrode materials prepared in Examples 1 and 2 at a current of 0.1 C; Figure 5 The rate performance and long cycle performance diagrams of the positive electrode materials prepared in Examples 1-2 and Comparative Examples 1-1, 1-2, and 1-3; Figure 6 The charge and discharge curves of the positive electrode materials prepared in Comparative Examples 2-1, 2-2, and 2-3 at a current of 0.1 C are shown. DETAILED DESCRIPTION
[0024] The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0025] The present invention will be further described below in conjunction with the accompanying drawings.
[0026] Example 1 The NFPP / C cathode material is prepared by the "ball milling-calcination" process using iron ore powder, phosphoric acid, sodium carbonate, and anhydrous glucose as raw materials. Among them, iron ore powder, phosphoric acid, sodium carbonate, and anhydrous glucose are iron sources, phosphorus sources, sodium sources, and carbon sources, respectively, and nitric acid is used as an oxidant and catalyst. The specific operation steps are as follows: 1) 23.43 g of iron ore concentrate and 46.12 g of phosphoric acid (H3PO4, 85 wt%) were added to 100 mL of dilute nitric acid (5 wt%) solution and stirred to obtain a mixed slurry. Then, the slurry was transferred to a ball mill, an appropriate amount of zirconium balls were added, and the slurry was milled at a speed of 300 RPM for 1 h to obtain material particles D. 50 White uniform suspension slurry <2 μm; 2) Mix 21.62 g sodium carbonate (Na2CO3) and 7.00 g anhydrous glucose (C6H 12 O6) were added to the ball mill slurry in sequence and stirred until no obvious bubbles were generated. The ball milling was continued at a speed of 300 RPM for 10 h to obtain material particles D 50 <0.3 μm uniform slurry; 3) The slurry obtained by ball milling was transferred to a 100°C oven for drying for 10 h to completely remove the moisture. After drying, the material was crushed with a high-speed grinder and sieved with a 300-mesh screen to collect finer precursor powder; 4) The precursor was loaded into a crucible and then sintered in a nitrogen atmosphere, first pre-sintered at 340°C for 2 h, then heated to 510°C for 9 h, with a heating rate of 3°C / min. After the material was cooled naturally, the NFPP / C composite cathode material was obtained.
[0027] Example 2 The NFPP / C cathode material is prepared by the "ball milling-calcination" process using iron ore powder, phosphoric acid, sodium dihydrogen phosphate, sodium carbonate, sucrose, and nitric acid as raw materials. Among them, iron ore powder is the only iron source, phosphoric acid is the main phosphorus source, sodium dihydrogen phosphate is a supplementary phosphorus source and a supplementary sodium source, sodium carbonate is the main sodium source, sucrose is the only carbon source, and nitric acid is used as an oxidant and catalyst. The specific operation steps are as follows: 1) Add 23.43 g of iron ore concentrate, 34.59 g of phosphoric acid (H3PO4, 85 wt%), and 12.12 g of sodium dihydrogen phosphate (NaH2PO4, 99 wt%) into 100 mL of dilute nitric acid (5 wt%) solution and stir to obtain a mixed slurry. Then transfer it to a ball mill, add an appropriate amount of zirconium balls, and mill at a speed of 300 RPM for 1 h to obtain material particles D. 50 White uniform suspension slurry <2 μm; 2) Mix 16.32 g sodium carbonate (Na2CO3) and 7.00 g sucrose (C12 H 22 O 11 ) was added to the ball mill slurry and stirred until no obvious bubbles were generated. The ball milling was continued at a speed of 300 RPM for 8 h to obtain material particles D 50 <0.3 μm uniform slurry; 3) The slurry obtained by ball milling was transferred to a 70°C oven for drying for 2 h to completely remove the moisture. After drying, the material was crushed with a high-speed grinder and sieved with a 300-mesh screen to collect finer precursor powder; 4) The precursor was loaded into a crucible and then sintered in a nitrogen atmosphere, first pre-sintered at 360°C for 3 h, then heated to 510°C for 11 h, with a heating rate of 3°C / min. After the material was cooled naturally, the NFPP / C composite cathode material was obtained.
[0028] Comparative Example 1-1 The only change on the basis of Example 1 is that no oxidant is added and the dilute nitric acid in step 1) of Example 1 is replaced with deionized water. The remaining steps are completely the same as Example 1.
[0029] Comparative Example 1-2 The only change on the basis of Example 1 is that the ball milling in step 1) in Example 1 is replaced with water bath heating, and the heating condition is 90° C. for reaction for 2 hours. The other steps are completely consistent with Example 1.
[0030] Comparative Examples 1-3 On the basis of Example 1, iron concentrate was used as the only iron source, and the composite sodium iron phosphate positive electrode material was synthesized by the "sand milling-spray drying-sintering" commonly used in industrial production. The specific operation steps are as follows: 1) 23.43 g iron ore powder, 48.48 g sodium dihydrogen phosphate (NaH2PO4), 6.36 g sodium carbonate (Na2CO3), 8.00 g ascorbic acid (C6H8O6) and 150 mL deionized water were added to a sand mill in sequence, and an appropriate amount of zirconium sand was added. The mixture was sand milled at a speed of 3000 RPM for 4 h to obtain material particles D. 50 <0.3 μm uniform suspension slurry; 2) The suspended slurry obtained by sand grinding was spray dried at an atomization frequency of 450 Hz, an inlet air temperature of 250°C, and an outlet air temperature of 120°C, and the dried precursor powder was collected; 3) The precursor was loaded into a crucible and then sintered in a nitrogen atmosphere, first pre-sintered at 400°C for 5 h, then heated to 550°C for 15 h at a heating rate of 3°C / min. After the material was cooled naturally, the NFPP / C composite cathode material was obtained.
[0031] Comparative Example 2-1 Weigh 23.96 g of iron oxide (Fe2O3), 48.48 g of sodium dihydrogen phosphate (NaH2PO4), 19.21 g of citric acid (C6H8O7), and 7.92 g of glucose (C6H 12 O6) was placed in a stirring kettle, and 150 mL of deionized water was added to stir and mix evenly; the mixed slurry was placed in a sand mill, and an appropriate amount of zirconium sand was added, and the mixture was sand milled at a speed of 2000 RPM for 1 h to obtain material D 50 <0.3 μm mixed slurry. The suspended slurry obtained by sand grinding was spray dried, the inlet air temperature was controlled at 200°C, the outlet air temperature was controlled at 100°C, and the dried precursor powder was collected. The precursor was transferred to a box furnace, nitrogen was continuously introduced, and the temperature was increased to 550°C at a heating rate of 3°C / min, and then kept warm for 12 h. After the material was cooled naturally, the NFPP / C composite positive electrode material was obtained.
[0032] Comparative Example 2-2 Weigh 121.2 g of ferric nitrate (Fe(NO3)3·9H2O), 48.48 g of sodium dihydrogen phosphate (NaH2PO4) and 8.5 g of ascorbic acid (C6H8O6) respectively and put them into 200 mL of deionized water, and stir them thoroughly until all the materials are completely dissolved. The obtained mixed solution is transferred to an 80°C water bath and stirred continuously until the water is completely evaporated. The evaporated mixture is ground and crushed with a grinder, and the dry powder is collected. The obtained powder is passed through a 300-mesh sieve to remove larger particles, and the sieved material is the final precursor. The precursor is transferred to a box furnace, nitrogen is continuously introduced, and it is pre-calcined at 300°C for 6 h, with a heating rate of 5°C / min. Then the temperature is raised to 500°C and calcined for 12 h, with a heating rate of 3°C / min. After the material is cooled naturally, the NFPP / C composite positive electrode material can be obtained.
[0033] Comparative Examples 2-3 Weigh 43.16 g of ferrous oxalate, 13.00 g of polyvinyl pyrrolidone, 23.24 g of ammonium dihydrogen phosphate (NH4H2PO4), 26.87 g of sodium pyrophosphate (Na4P2O7) and 11.48 g of citric acid and add them to 200 mL of deionized water in turn, and stir thoroughly until all materials are completely dissolved. The obtained mixed solution is transferred to an 80°C water bath and stirred continuously until the water is completely evaporated. The evaporated mixture is ground and crushed with a grinder, and the dry powder is collected. The obtained powder is passed through a 300-mesh sieve to remove larger particles, and the sieved material is the final precursor. The precursor is transferred to a box furnace, nitrogen is continuously introduced, and the temperature is raised to 550°C at a heating rate of 3°C / min, and then kept warm for 12 h. After the material is cooled naturally, the NFPP / C composite positive electrode material can be obtained.
[0034] Test Example 1 The positive electrode composite materials prepared in Example 1, Example 2, Comparative Example 1-1, and Comparative Example 1-3 were observed under a scanning electron microscope. The observation results are as follows: Figure 1 As shown in the figure, it can be seen that the sample particles of Example 1 and Comparative Example 1-1 are irregular particles, and the particle size distribution is between 0.2 and 1 μm. Example 2 and Comparative Example 1-3 present spherical morphology, and the secondary particle size distribution is between 5 and 10 μm.
[0035] Test Example 2 The positive electrode composite materials prepared in Example 1, Example 2, Comparative Example 1-1, Comparative Example 1-2 and Comparative Example 1-3 were subjected to X-ray diffraction test, and the results were as follows: Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the samples of Example 1 and Example 2 have no obvious impurities, indicating that the purity of Na4Fe3(PO4)2(P2O7) is relatively high. Figure 3 As shown, there is obvious NaFePO4 impurity phase in Comparative Example 1-1, Comparative Example 1-2 and Comparative Example 1-3.
[0036] Test Example 3 The positive electrode composite materials prepared in Examples 1 and 2 were tested for specific capacity at a voltage of 2.0-4.0 V. The results are as follows: Figure 3 , Figure 4 As shown; the positive electrode composite materials in Examples 1 to 4 and Comparative Examples 1 to 3 were placed in button batteries and their electrochemical properties were tested. The results are shown in Table 1.
[0037] Table 1 Electrochemical properties of various cathode composite materials
[0038] contrast Figure 3 , Figure 4 As shown in Table 1, the first charge specific capacities of Example 1 and Example 2 at 0.1 C current are 108.2 and 106.7 mAh / g, respectively, and the first discharge specific capacities are 103.4 and 101.5 mAh / g, respectively; the capacity retention rates of Example 1 and Example 2 after 50 cycles at 1 C rate are 99.2% and 99.8%, respectively; As shown in Table 1 and Figure 3 , 4 It can be seen that the reversible capacities of the positive electrode materials prepared in Examples 1 and 2 at 0.1 C are 103.4 and 101.5 mAh / g, respectively.
[0039] However, using the same raw materials but slightly changing the synthesis process, the comparative examples prepared showed significantly deteriorated sodium storage performance. As shown in Table 1, in Comparative Example 1-1, the oxidant in the pre-reaction stage was removed, and the first charge and discharge specific capacities of the prepared materials at 0.1C current were 94.3 and 85.9 mAh / g, respectively. In Comparative Example 1-2, the ball milling step in the pre-reaction stage was changed to a heating reaction, and the first charge and discharge specific capacities of the prepared materials at 0.1C current were 63.6 and 60.2 mAh / g, respectively. In Comparative Example 1-3, the conventional sand milling spray drying process was used, and the first charge and discharge specific capacities of the prepared materials at 0.1C current were 72.6 and 67.7 mAh / g, respectively.
[0040] Test Example 4 The electrochemical performance and BOM cost analysis of the positive electrode materials prepared in Example 1 and Comparative Example 2 were performed, and the results are shown in Tables 1 and 2.
[0041] As shown in Table 1, compared with the iron red route (Comparative Example 2-1), the performance of the embodiment prepared by the iron concentrate technical route provided by the present invention is significantly better. Compared with ferric nitrate (Comparative Example 2-2) and the iron oxalate route (Comparative Example 2-3), the NFPP product produced by the technology of the present invention also shows comparable performance, and is significantly better in the first effect. Even at a current of 1 C, Examples 1 and 2 produced by the technology of the present invention can provide a reversible capacity of more than 90 mAh / g, and a 50-cycle cycle retention rate of more than 99%, showing an excellent application foundation.
[0042] Table 2 Synthesis process and BOM cost analysis of NFPP materials prepared by different technical routes
[0043] As shown in the results of Table 2, according to the formula provided in Example 1, it is estimated that 0.37 t of iron ore powder, 0.74 t of 85 phosphoric acid and 0.35 t of Na2CO3 are required to produce 1 t of sodium ferric pyrophosphate, but because the price of iron concentrate raw materials is extremely low, only 2,000 yuan / ton, the final material BOM is only 7,700 yuan / ton. Compared with the iron red process, although the two routes use similar production processes, the BOM cost alone can be reduced by 16.3%. Compared with the ferric nitrate and iron oxalate routes, in addition to the BOM cost being reduced by 35.2% and 54.6% respectively, the manufacturing and processing advantages are also significant. For example, the technical route using ferric nitrate and ferrous oxalate as the main raw materials often adopts a more complex synthesis process, such as the sol-gel method, which has high processing difficulty and processing energy consumption. At the same time, the ferric nitrate and iron oxalate routes also have serious waste gas emissions, such as NO x , CO and other greenhouse gases.
[0044] Although the present invention is described herein with reference to specific embodiments, it should be understood that these embodiments are merely examples of the principles and applications of the present invention. It should therefore be understood that many modifications may be made to the exemplary embodiments and that other arrangements may be devised without departing from the spirit and scope of the present invention as defined by the appended claims. It should be understood that the various dependent claims and features described herein may be combined in a manner different from that described in the original claims. It should also be understood that features described in conjunction with individual embodiments may be used in other described embodiments.
Claims
1. A method for preparing a low-cost composite sodium iron phosphate positive electrode material, characterized in that: The steps include: S1, adding iron ore concentrate powder, phosphorus source and oxidant into deionized water in sequence and grinding to obtain an iron phosphate precursor; S2, adding a carbon source and a sodium source into the iron phosphate precursor and stirring to obtain a solid-liquid mixed slurry; S3, ball milling / sand milling the solid-liquid mixed slurry to obtain a uniformly dispersed slurry; S4, sequentially drying, crushing and sieving the uniformly dispersed slurry to obtain a precursor powder; S5. Sintering the precursor powder in an inert gas to obtain the low-cost composite sodium iron phosphate positive electrode material.
2. The method for preparing a low-cost composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: In the S2, the solid content in the solid-liquid mixed slurry is 20~50 wt%; in the S4, the drying includes air drying and spray drying, the air drying temperature is 70~100°C, the air drying time is 2~10 h, the spray drying inlet temperature is 150~250°C, the outlet temperature is 60~120°C, and the feed rate is 0.5~30 mL / min; in the S5, the sintering includes pre-sintering and two-stage sintering, the pre-sintering temperature is 300~400°C, the pre-sintering time is 2~5 h, the two-stage sintering temperature is 480~550°C, and the two-stage sintering time is 6~15 h.
3. The method for preparing a low-cost composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: The inert gas is nitrogen, argon, an argon-hydrogen mixture or a nitrogen-hydrogen mixture.
4. A low-cost composite sodium iron phosphate positive electrode material, characterized in that: The invention comprises iron ore concentrate powder, a phosphorus source, an oxidant, a sodium source and a carbon source, wherein the iron content of the iron ore concentrate powder is 71-72 wt%.
5. The low-cost composite sodium iron phosphate positive electrode material according to claim 4, characterized in that: The invention comprises the following raw materials in parts by weight: 20-25 parts of iron ore concentrate powder, 29-52 parts of phosphorus source, 4-5 parts of oxidant, 18-22 parts of sodium source and 6-8 parts of carbon source.
6. The low-cost composite sodium iron phosphate positive electrode material according to claim 4, characterized in that: The phosphorus source includes at least one of phosphoric acid, sodium dihydrogen phosphate, pyrophosphoric acid, disodium dihydrogen pyrophosphate, and sodium pyrophosphate.
7. The low-cost composite sodium iron phosphate positive electrode material according to claim 4, characterized in that: The oxidant includes at least one of nitric acid, sodium nitrate, ammonium nitrate, nitrous acid, sodium nitrite, and ammonium nitrite.
8. The low-cost composite sodium iron phosphate positive electrode material according to claim 4, characterized in that: The carbon source includes at least one of starch, glucose, sucrose, citric acid and ascorbic acid.
9. The low-cost composite sodium iron phosphate positive electrode material according to claim 4, characterized in that: The sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium nitrate, sodium dihydrogen phosphate, disodium dihydrogen pyrophosphate, and sodium pyrophosphate.
10. A cathode material obtained by the method for preparing a low-cost composite sodium iron phosphate cathode material according to any one of claims 1 to 3, or use of the low-cost composite sodium iron phosphate cathode material according to any one of claims 4 to 9 in preparing a sodium ion battery.